1991
DOI: 10.1083/jcb.113.6.1371
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of early events in acetylcholine receptor assembly.

Abstract: Abstract. Mammalian cell lines expressing nicotinic acetylcholine receptor (AChR) subunit cDNAs fromTorpedo californica were used to study early events in AChR assembly. To test the hypothesis that individual subunits form homooligomeric intermediates before assembling into u2fl~ pentamers, we analyzed the sedimentation on sucrose density gradients of each subunit expressed separately in cell lines. We have shown previously that the acute temperature sensitivity of Torpedo AChR subunit assembly is due, in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 45 publications
3
37
0
1
Order By: Relevance
“…In the case of mutant CFTR protein, the efficiency of cellular membrane integration declines to ,25% that of the wild-type protein (Kopito, 1999). Similar observations have been made for a number of other integral membrane proteins, such as epithelial sodium channel (ENaC), band 3 anion exchanger (SLC4A1) and nicotinic acetylcholine receptor (CHRNA) (Paulson et al, 1991;Rajan et al, 2001;Valentijn et al, 1998). Protein folding and stability studies have demonstrated that a single amino acid change is sufficient to reduce the folding efficiency in a protein from 50% at body temperature to below 10% (Guerois et al, 2002).…”
Section: Introductionsupporting
confidence: 53%
“…In the case of mutant CFTR protein, the efficiency of cellular membrane integration declines to ,25% that of the wild-type protein (Kopito, 1999). Similar observations have been made for a number of other integral membrane proteins, such as epithelial sodium channel (ENaC), band 3 anion exchanger (SLC4A1) and nicotinic acetylcholine receptor (CHRNA) (Paulson et al, 1991;Rajan et al, 2001;Valentijn et al, 1998). Protein folding and stability studies have demonstrated that a single amino acid change is sufficient to reduce the folding efficiency in a protein from 50% at body temperature to below 10% (Guerois et al, 2002).…”
Section: Introductionsupporting
confidence: 53%
“…5, B and D). The subunits migrated broadly across the gradients, as previously observed for unassembled AChR subunits (40), appearing in fractions 3-4 where subunit monomers are expected to migrate and continuing to the bottom fractions. The migration of the subunits is consistent with the formation of heterogeneous homo-oligomers of the subunits and/or associations with chaperone proteins such as CN (see also Ref.…”
Section: N-linked Glycans and Nicotinic Receptor Assemblymentioning
confidence: 49%
“…The nascent subunit polypeptide subsequently undergoes cleavage of its signal sequence, oxidation of its disulfide bonds (Mishina et al, 1985;Blount and Merlie, 1990), and N-glycosylation of specific residues (Merlie et al, 1982;Smith et al, 1987;Blount and Merlie 1988). Chaperones such as binding protein BiP (Blount and Merlie, 1991;Paulson et al, 1991;Forsayeth et al, 1992) and calnexin (Gelman et al, 1995;Keller et al, 1996Keller et al, , 1998 promote proper folding and maturation of AChR subunits. Unassembled or misfolded AChR subunits are then targeted for degradation by the ER-associated proteasomal degradation machinery (Wanamaker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%